問題導向學習對法律系大學生問題解決能力及自我導向學習之研究 Problem-Based Learning on the Problem-Solving Ability and Self-Directed Learning of Undergraduate Students - 楊心怡 Hsin-I Yu; 李啟嘉 Chi-Chia Lee (National Taiwan Normal University, 2015)
本研究旨在探討問題導向學習對大學生的問題解決能力與自我導向學習之影響。研究對象為臺北市某大學法律系65 位學生，隨機選取一班為實驗組實施問題導向學習，另一班為控制組接受講述為主的教學。以「問題解決創造力測驗」與「自我導向學習量表」為本研究評量工具。研究結果發現，實驗組在「問題解決創造力測驗」總得分顯著高於控制組，其中以「字詞聯想」、「成語替換」、「情境式問題解決」、「不合理圖形覺察」四個向度之得分顯著高於控制組。顯示問題導向學習能有效提升學生的問題解決能力。此外，實驗組在自我導向學習量表的「效率學習」、「喜愛學習」、「主動學習」的得分顯著高於控制組。本研究根據上述研究結果歸納以下結論：以問題為根基能激發學生的學習興趣並增進對問題瞭解的深度及廣度，有助於提升學生問題解決能力、思考能力及厚實專業基礎。對於擁有高度學習自主權的大學生在小組腦力激盪及討論過程，深度瞭解學習議題及整合新舊知識，達到相互支援及相互學習，有助於培養自我導向學習能力，對於日後踏出校園面臨工作之挑戰有所助益。 This study examined the effects of problem-based learning on the problem-solving ability and self-directed learning tendency of undergraduate students. A total of 65 undergraduate law students were recruited and randomly assigned to experimental and control groups. Empirical data showed that the students in the experimental group who received problem-based learning demonstrated significantly stronger performance than those in the control group in problem-solving measurement, particularly in word association, idiom substitution, and situational problem-solving subscales. In addition, the experimental group demonstrated significantly strong performance in efficiency learning, such as on the learning and active learning subscales of self-directed learning. The theoretical and practical implications of the findings are discussed.